Implementacija arhivskih pomožnih ved v arhivsko teorijo in prakso - Klasinc, Peter Pavel (Atlanti, 2023)
Purpose: When preparing the materials for the accreditation of the study pro-gram at the first Bologna level of Archival Studies (VS, graduate archivist), a group of archival experts proposed that the course Auxiliary Archival Science be included among the optional subjects of this study. We were led to this decision by the desire to provide future graduate archivists with as much knowledge as possible, which they will be able to profitably use either in archival professional work in professional archives or in the operation of archival services for creators of archival and documentary material.Methods: In the research we used multiple methods to reach our goal, such as descriptive method, a summary method, an analysis method, a historical method, and an experiential method was also implemented.Results: The results are reflected in the entire presentation of archival auxiliary sciences, which are defined mostly in historical literature, so we adapted and justified them as individual sciences in archival science, archival science and archival theory and practice.Conclusions: Based on the decision regarding the importance of archival aux-iliary sciences, we included the subject in the first-level study of Archival Stud-ies at Alma Mater Europaea in the initial phase among the optional subjects. The experience so far has shown a lot of interest in this course among first-cy-cle students, and it has been found that interesting seminar assignments have also been created.
Keywords: archival auxiliary sciences; archival science; archivistica; arhivska znanost; arhivske pomožne vede; conoscenza; definition; definizione; development; giustificazione; justification; knowledge; opredelitev; razvoj; scienze ausiliarie archivi-stiche; sviluppo; utemeljitev; znanje